Advocacy Assistance for Patients' Families' Civil Law Rights in Alleged Medical Disputes in Sorong City: Pendampingan Advokasi Hak Keperdataan Keluarga Pasien pada Dugaan Sengketa Medis di Kota Sorong - Hasriyanti Hasriyanti; Nurul Fajeriana; Muhammad Arifin Abd. Kadir; Hadi Tuasikal; Akhmad Faqih Mursid; Mulyadi Golap (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The right to information and access to medical records constitutes a fundamental component of patients' civil law rights as guaranteed under Law Number 17 of 2023 on Health in Indonesia. However, information asymmetry between healthcare providers and patients and their families in alleged medical disputes continues to limit public understanding of legal rights and appropriate dispute resolution mechanisms. This Community Service Program aimed to enhance the legal literacy of patients' families regarding their right to information and access to medical records while strengthening their bargaining position through a non-litigation advocacy approach. The program involved six family members of a patient facing an alleged medical dispute in Sorong City. The implementation consisted of three stages: preparation, advocacy, and evaluation. The preparation stage involved identifying legal facts through in-depth interviews and document analysis. The advocacy stage included legal counseling, communication assistance, and facilitation of requests for information and access to medical records from healthcare providers. The evaluation stage assessed improvements in participants' legal understanding and the progress of the advocacy process. The results showed that the advocacy assistance improved the legal understanding of all six participants regarding patients' civil law rights, strengthened their ability to exercise their rights to information and medical records in accordance with applicable laws and regulations, and promoted more constructive communication with healthcare providers. This community service program demonstrates that civil law rights-based advocacy assistance is an effective community empowerment strategy for supporting more transparent, equitable, and patient-centered resolution of alleged medical disputes.